THE INFLUENCE OF REPRODUCTIVE HEALTH PROMOTION ON INCREASING THE KNOWLEDGE OF SANTRI AT THE ANSHORUSSUNNAH MANTINGAN ISLAMIC BOARDING SCHOOL - Farras Kens Daryngga; Arif Widodo (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: School is a place to obtain education and knowledge about reproductive health for teenagers. One of the educational models in Indonesia is Islamic boarding schools. Objectives: This research was conducted on 75 students of the Anshorussunnah Islamic Boarding School, Mantingan District, Ngawi Regency, research location in Ngrancang Village RT0 03 RW 06. Methods: This research is a type of quantitative research with a research design using a quasi-experimental approach with only pre-test post-test. Data analysis with Wilcoxon. Results: Based on the results of data analysis, after carrying out the Wilcoxon test, it was found that 75 research respondents experienced an increase in their scores. Conclusions: The results of testing the data above show the results (Asymp.sig. (2-tailed)) = 0.001 < α (0.05), so it can be concluded that there is a significant difference between the knowledge of students before and after the intervention given, namely counseling on adolescent reproductive health and premarital sexual intercourse in results of pre-test and post-test scores.